A True Experimental Study to Assess the Effectiveness of Helfer Skin Tap Technique on the Level of Pain during Intramuscular Injection of Tetanus Toxoid among Antenatal Mothers in a selected Hospital of Delhi (International Journal of Nursing Education, 2020)
A True experimental study was conducted to assess the effectiveness of Helfer skin tap technique on the level of pain during intramuscular injection of Tetanus Toxoid among Antenatal Mothers in a selected Hospital of Delhi and to find out the association between the level of pain experienced by Antenatal Mothers during intramuscular injection using Helfer skin tap technique and selected variables. A total of sixty sample were randomly assigned into 2 groups (30 in experimental group and 30 in control group)using simple random sampling technique. Structured interview schedule was used to collect the demographic characteristics and clinical health data. For the administration of intramuscular injection, Helfer skin tap technique was used for the experimental group and routine technique was used for the control group. Immediately after the administration, the post test pain score was obtained using Numeric pain rating scale. Findings revealed that the mean post test pain score and standard deviation of the experimental group was 1.13 ±1.11 whereas of the control group was 4.23±2.01. The calculated ‘t’ test value 4.42 was found significant at p? 0.05. Significant association was found between the level of pain experienced by Antenatal Mothers during intramuscular injection with Helfer skin tap technique and selected variables such as religion and Body Mass Index but no association was found with other selected variables. The study results showed that Helfer skin tap technique was effective in reducing the level of pain during intramuscular injection.